A Critical Discourse Analysis of the Electoral Talks of Iranian Presidential Candidates in 2013. (24th June 2015) - Gowhary, Habib; Rahimi, Farahnaz; Azizifar, Akbar; Jamalinesari, Ali
Abstract: On Friday, 14 June 2013 one of the most significant events of Iran and the Middle East happened: the presidential election of Iran. The 11th president of Iran started his term on 3rd August 2013. The election was in fact a competition between two main parties: Principlist and Reformist. This paper studied the speeches of the nominees of these two parties: Mohammad Bagher Ghalibaf and Hassan Ruhani. We selected one of their speeches on their election campaigns and incorporated their statements and stances in the framework of CDA introduced by Norman Fairclough. The results showed that the two nominees took two opposite strands on the same events. They used language as a means of promoting their own social, political, personal interests and as an effective means for power struggle.